Changing patterns of conspicuous consumption: Media representations of luxury in second homes. (August 2019) - Walters, Trudie; Carr, Neil
This article examines the potential of utilising representations of luxury in second homes to chart the changing patterns of conspicuous consumption. It is situated within a New Zealand context and based on the analysis of representations of luxury in second homes in an architecture/lifestyle magazine from 1936 to 2015. A qualitative thematic analysis was carried out on the written and visual text of 305 second home articles. The findings are divided into time periods which relate to distinct socio-cultural, political and economic events and ideologies that have influenced New Zealand society. The analysis reveals a change from 'quiet luxury' during the war years to the luxury of imported products, reflecting a fascination with first American and then European style in the mid-century. It also shows a change from a reputed cultural reticence to display one's wealth to the flagrant conspicuous consumption of luxury goods and services in the 1980s which aligns with the rise of new wealth after the introduction of neoliberalism in the country. Finally, the variance between representations of luxury during recessionary times in the 1970s and 2000s demonstrates a change in attitude towards conspicuous consumption.